Data and Market Power - Eeckhout, Jan,Veldkamp, Laura (National Bureau of Economic Research, 2022)
Might firms' use of data create market power? To explore this hypothesis, we craft a model in which economies of scale in data induce a data-rich firm to invest in producing at a lower marginal cost and larger scale. However, the model uncovers much richer interactions between data, welfare and market power. Data affects risk, firm size and the composition of the goods firms produce, all of which affect markups. The tradeoff between these forces depends on the level of aggregation at which markups are measured. Empirical researchers who measure markups at the product level, firm level or industry level come to different conclusions about trends and cyclical fluctuations in markups. Our results reconcile and re-interpret these facts. The divergence between product, firm and industry markups can be a sign that firms are using data to reallocate production to the goods consumers want most
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Daten; Marktmacht; Mark-up Pricing; Skalenertrag; Information; Knowledge; and Uncertainty; Prices; Business Fluctuations; and Cycles; General